Enhancing Teacher Motivation and Job Satisfaction at SHS 1 Timpeh, Dharmasraya Regency: Strategies for Better Educational Outcomes - Ningsih, Setya; Ahyarti, Ayra; Gistituati, Nurhizrah; Nellitawati, Nellitawati; Achyar, Novriyanti (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to explore strategies for enhancing teacher motivation and job satisfaction at Senior High School (SHS) 1 Timpeh, Dharmasraya Regency, as a means to improve the overall quality of education. Employing a mixed-method approach, the study integrates qualitative insights from literature analysis with quantitative data from a survey. The survey involved a Likert-scale questionnaire distributed to all teachers at SHS 1 Timpeh, focusing on eight key factors influencing motivation and satisfaction: teaching quality, management support, work environment, professional development, recognition, interpersonal relationships, workload, and opportunities for innovation. Data analysis revealed that teaching quality (average score 4.2, 85% agreement), interpersonal relationships (4.1, 82%), and a positive work environment (4.0, 80%) were the most influential factors, in fostering motivation and satisfaction. However, workload (2.7, 40%) and limited access to professional development (3.5, 65%) were identified as significant challenges. Based on these findings, the study recommends implementing continuous training programs, establishing a fair reward system, and improving communication between management and teachers. These strategies aim to create a more supportive and productive work culture, reducing stress and enhancing motivation among educators. Ultimately, this study provides actionable insights for stakeholders to prioritize teacher welfare and achieve better educational outcomes.